Nursing with a Message - D'Antonio, Patricia (Rutgers University Press, 2021)
Nursing with a Message transports readers to New York City in the 1920s and 1930s, charting the rise and fall of two community health centers in the neighborhoods of East Harlem and Bellevue-Yorkville. Award-winning historian Patricia D’Antonio examines the day-to-day operations of these clinics, as well as the community outreach work done by nurses who visited schools, churches, and homes encouraging neighborhood residents to adopt healthier lifestyles, engage with preventive physical exams, and see to the health of their preschool children. As she reveals, these programs relied upon an often-contentious and fragile alliance between various healthcare providers, educators, social workers, and funding agencies, both public and private. Assessing both the successes and failures of these public health demonstration projects, D’Antonio also traces their legacy in shaping both the best and worst elements of today’s primary care system.